SYDNONE DERIVATIVES A SYNTHONS FOR NOVEL MESOIONIC COMPOUNDS. SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL EVALUATION OF SOME 2-(4`-SUBSTITUTED ANILINOSYNDON-3`-YL)-1, 3, 4-THIADIAZINO (6, 5-B) INDOLES - Hemant Panwar; Shishupal Singh; Nidhi Chaudhary (Universitas Gadjah Mada, 2011)
In the present study, a series of 2-(4´-Substitutedanilinosydnon-3´-yl)-1, 3, 4-thiadiazino (6, 5-b) indoles 7a-j have been synthesized. All the synthesized compounds have been characterized by elemental and spectral (I R, 1H- NMR and Mass) spectrometric analysis. Furthermore, above mentioned compounds were evaluated for their antibacterial and antifungal activities against selected panel of pathogenic strains. Ampicillin trihydrate, ofloxacin and fluconazole, griseofulvin were used as standard drugs for antibacterial and anifungal activity respectively. Compound 7j was found the most potent one with lesser toxicity in the prepared indole derivatives.